Entropy vs. CRITIC Weighting for TOPSIS Ranking of Mobile Data Packages in Ambon City - Vederico Pitsalitz Sabandar; Sanriomi Sintaro; Wisard Widsli Kalengkongan; Jumriadi; Sitti Nur Isnian (Informatics and Software Engineering, 2025)
This study proposes a decision-support approach for selecting prepaid mobile data packages in Ambon City that balances price, main quota, and validity period. Twelve packages from Telkomsel, XL, Indosat IM3, and Tri were evaluated using four criteria: price, main quota, validity, and price per main gigabyte. TOPSIS was used for ranking, and Entropy and CRITIC were compared as objective weighting methods to examine the effect of weighting choice. Entropy emphasized the main quota, producing a quota-focused evaluation. CRITIC gave greater weight to price and price efficiency, accounting for data variation and criterion correlations. Both methods selected Tri Happy 70GB as the best option. The overall rankings were highly consistent, with a Spearman rank correlation of 0.8741, although some alternatives changed positions within the top group. The analysis is limited to a single time snapshot based on published package attributes and excludes measured network performance in Ambon City. In practice, the framework is transparent, replicable, and can be extended with constraints such as maximum budget and minimum validity requirements. The study contributes a controlled comparison of Entropy and CRITIC effects while keeping TOPSIS constant.